A novel termination site in a case of Stüve–Wiedemann syndrome: case report and review of literature - Bhalla, Deepali; Sati, Sunil; Basel, Donald; Karody, Vijender (Frontiers in Pediatrics, 2024)
Stüve-Wiedemann syndrome (SWS) is a rare autosomal recessive disorder that is characterized by bowing of long bones, dysautonomia, temperature dysregulation, swallowing and feeding difficulties, and frequent respiratory infections. Respiratory distress and hyperthermic events are the leading causes of early neonatal death, and most patients are not expected to survive past infancy. Here, we report on the survival of a 5-year-old male with SWS, discussing his case presentation, providing a brief clinical course, and discussing the outcome. This case adds to the literature surrounding rare instances of childhood survivors of SWS and raises awareness for this syndrome to facilitate an earlier recognition, intervention, and genetic counseling for the families, thereby improving understanding of this disease and the health outcomes for the children affected by this condition.